2021
DOI: 10.1039/d0cc07970g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in perovskite oxides as electrode materials for supercapacitors

Abstract: Owing to the high power density and ultralong cycling life, supercapacitors represent the alternative to electrochemical batteries in energy storage applications. However, the relatively low energy density is the main...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 145 publications
1
109
0
Order By: Relevance
“…27,28 Hence the performance of perovskites can be improved through the creation of oxygen vacancies. This can be achieved through doping the perovskites with impurities; 29,30 another way is to create a porous structure as it gives a shorter diffusion path, a large specific area, and the rapid transportation of ions. 13,22,23,31 However, synthesizing porous perovskite oxides is tedious.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Hence the performance of perovskites can be improved through the creation of oxygen vacancies. This can be achieved through doping the perovskites with impurities; 29,30 another way is to create a porous structure as it gives a shorter diffusion path, a large specific area, and the rapid transportation of ions. 13,22,23,31 However, synthesizing porous perovskite oxides is tedious.…”
Section: Introductionmentioning
confidence: 99%
“…19 Perovskites have good ionic conductivity and thermal stability owing to the defects associated with the crystal lattice, as well as high electron mobility, and hence they find extensive use as catalysts. 21 Owing to its good stability, ion/electron transport, and redox features, LaMnO 3 has also recently been considered as a supercapacitor electrode 22–26 and as a catalyst for the oxygen reduction reaction. 27,28 For example, Mo et al prepared calcium-doped LaMnO 3 by sol–gel synthesis and found that the supercapacitor device could deliver a specific energy of 7.6 W h kg −1 at a low power density of 160 W kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors (SCs) as a unique energy device play an important role in terms of the clean energy portfolio. At present, for improving energy and power density, a lot of pseudocapacitive electrode materials are extensively explored, such as transition metal oxides, MXene, hydroxyls, carbide, nitride, conductive polymer, and so on. , In the case of transition metal oxides, they realize Faradaic charge storage through the changing metal oxidation state, and therefore, most of transition metal oxides present a poor cycle life on account of volume changes during the electrochemical process. In addition, the transition metal oxides, as inorganic compounds, are generally nonrenewable in the natural environment and are obtained by using synthesis (or extraction) techniques harmful to the ecosystem . For achieving the predicted extensive use of SCs, exploring the type of new green electrode materials becomes a key solution.…”
Section: Introductionmentioning
confidence: 99%